STRATEGI PEMENANGAN CALEG PARTAI GERINDRA DALAM PEMILU LEGISLATIF 2019: STUDI KASUS BAMBANG PUJIANTO DAPIL 2 SIDOARJO - Bintang Widiowati; Wisnu Pramutanto (Universitas Airlangga, 2020)
The present study discusses the strategy of winning the Gerindra party candidates in Sidoarjo. In this case the problem that occurs is the struggle for the seat of Si- doarjo regency DPRD. In this thesis the researcher will explain the winning strat- egies, challenges and obstacles during the campaign process of the Gerindra party candidates. Seeing within the framework of the theory of Firmanzah which states that political marketing is divided into 4 programs (4P) namely: Product, Promo- tion, Price, Place. In this research, it will be seen how the winning strategy carried out by the Gerindra party candidates (Bambang Pudjianto) in electoral districts 2 of Sidoarjo regency, where he is an incumbent candidate who has advanced as a people's representative. His strategy is to rely on 3 products of political jargon; # win us, the medical check-up program and aspiration stalls that reap the enthusias- tic response of citizens. With the strategy carried out by Bambang Pudjianto, he succeeded in attracting the sympathy of the people so that he was re-elected as the sidoarjo district parliament.